Gaya Komunikasi Pimpinan dengan Pegawai dalam Menangani Kasus Narkoba di Kantor BNN Kabupaten Karo - Tambunan, Annisa Putri; Suharyanto, Agung (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to determine the leadership communication style applied by the Head of the Karo Regency BNN with employees in handling drug cases at the Karo Regency BNN office. This research uses the Behavioral Theory of Gage and Berliner to see what kind of communication style is carried out by the Head of BNN in an effort to handle drug cases at the Karo Regency BNN Office. This research uses a qualitative approach where researchers explain the data obtained through observation, documentation, and interviews to obtain more detailed information. The analysis process used in this research is based on the Miles and Huberman model through the process of data reduction, data presentation, and conclusion drawing. The result of this research is that the Head of the Karo Regency BNN uses 3 types of communication styles in his leadership, namely first the relingushing style, second the structuring style and finally the equalitarian style. In this case The relingushing style is a communication style that dominates the communication style possessed by the Head of BNN Karo in his leadership as evidenced by democratic communication and provides opportunities for all employees to convey aspirations and performance reporting in the success of superior programs built at the Karo Regency BNN Office.